The betrayal knows my name. 8 - Odagiri, Hotaru (Yen Press, 2018)
"Reiga reveals the truth behind the Sunset of the Underworld, the cataclysmic event that led to the interminable conflict between him and the Giou clan more than a thousand years ago. What happened to Yuki, Luka, and Takashiro at the beginning? In this war of betrayals, what fate awaits the soldiers...?"--Page [4] of cover.